Annika Zorn, Jeff Haywood and Jean Claude Glachant (2018). Higher Education in the Digital Age. Edward Elgar Publishing - Dávila Morán, Roberto Carlos (Revista de la Universidad del Zulia, 2021)
Reseña del libro: Annika Zorn, Jeff Haywood and Jean Claude Glachant (2018). Higher Education in the Digital Age. Edward Elgar Publishing A cargo de: Roberto Carlos Dávila Morán